Alzheimer’s Disease: Current and Future Treatments. A Review - Chou, Evelyn (International Journal of Medical Students, 2014)
Alzheimer’s disease (AD) is a currently incurable neurodegenerative disorder whose treatment poses a big challenge. Proposed causes of AD include the cholinergic, amyloid and tau hypotheses. Current therapeutic treatments have been aimed at dealing with the neurotransmitter imbalance. These include cholinesterase inhibitors and N-Methyl-D-aspartate (NMDA) antagonists. However, current therapeutics have been unable to halt AD progression. Much research has gone into the development of disease-modifying drugs to interfere with the course of the disease. Approaches include secretase inhibition and immunotherapy aimed at reducing plaque deposition. However, these have not been successful in curing AD as yet. It is believed that the main reason why therapeutics have failed to work is that treatment begins too late in the course of the disease. The future of AD treatment thus appears to lie with prevention rather than cure. In this article, current therapeutics and, from there, the future of AD treatment are discussed.